Studi Analisis Makna "Merdeka" Menurut Surat Galatia Dan Implementasinya Bagi Orang Percaya Masa Kini - Baskoro, Paulus Kunto (DIDASKO: Jurnal Teologi dan Pendidikan Kristen, 2024)
Many believers today are still trapped in living with the customs that apply in a culture or human regulations. So even though you believe in Jesus, you are still bound by the old human way of life. Makes the life of every believer not experience true freedom. In fact, Jesus' sacrifice and redemption perfected life as a whole. That is why the Letter of Galatians is an important reference for analyzing the life of a believer who is free in Christ as a whole, so that life does not depend on customs. As Paul stated, a person who obeys the law is like a slave who is enslaved. Therefore, freedom becomes one of the central teachings of Galatians. This research uses descriptive qualitative methods. The purpose of this writing is, first, to explain the biblical principle of independence. Second, emphasizing the concept of independence in the implementation of the lives of believers today, so that believers' lives are not bound by human customs.AbstrakBanyak orang percaya masa kini masih terjebak dengan kehidupan dengan tata adat istiadat yang berlaku dalam sebuah kebudayaan atau peraturan-peraturan manusia. Sehingga meskipun sudah percaya Yesus, namun masih terikat dengan tata cara hidup manusia lama. Membuat kehidupan setiap orang percaya tidak mengalami kemerdekaan yang sesungguhnya. Padahal pengorbanan dan penebusan Yesus menyempurnakan kehidupan secara utuh. Itu sebabnya Surat Galatia menjadi acuan penting untuk menganalisis kehidupan orang percaya yang merdeka dalam Kristus secara utuh, sehingga hidup tidak tergantung kepada adat istiadat. Seperti yang dinyatakan Paulus, orang yang melakukan hukum Taurat ibarat seorang hamba yang diperbudak. Maka dari itu kemerdekaan menjadi salah satu pusat ajaran dari surat Galatia ini. Penelitian ini menggunakan metode kualitatif deskritif. Tujuan dari penulisan ini, Pertama, menjelaskan prinsip merdeka yang biblical. Kedua, menekankan konsep merdeka dalam implementasi kehidupan orang percaya masa kini, sehingga hidup orang percaya tidak terikat dengan adat istiadat manusia.